Pendekatan Kontekstual Dalam Tugas Misi Dan Komunikasi Injil Pasca Pandemi Covid-19 - Yakob Tomatala (Jurnal Teologi Kontekstual Indonesia, 2021)
God reveals Himself in contextual ways. In revealing Himself, He sets forth to do His will and through His will, God materializes His word. Furthermore, God’s sovereign will is revealed in contextual ways in terms of today’s community life in regards to the history of every human civilation. God’s contextual self disclosure is not just an instrument that is used to display the essence of God, but it is also a method to comprehend His substance. In relation to God’s self disclosure, the contextualized self disclosure of God provides a basis for implementing His mission through bringing and communicating the Gospel to every community context. This concept is thoroughly explained within the discourse about “The contextual approach in doing missions and communicating the Gospel in Post Covid-19 Pandemic era”. This research underlies several important issues. These issues includes : First, Contextual Approach in Doing Missions; Second, Contextual Approach in Communicating the Gospel in Post Covid-19 Pandemic era. Hopefully through this discourse there is a broad overview about implementing the Great Commission of Christ Jesus in a contextual way in today’s world specifically in the Post Covid-19 period. ABSTRAKPenyataan TUHAN Allah dalam sejarah adalah kontektual. Penyataan Allah yang kontekstual melibatkan kehendak-Nya yang berdaulat sebagai landasan dari semua tindakan-Nya. Pada sisi lain, penyataan TUHAN yang berdaulat dinyatakan-Nya secara kontektual pada konteks kehidupan kekinian dalam sejarah setiap masyarakat. Penyataan TUHAN yang kontekstual bukan saja sebagai cara penyataan diri-Nya, tetapi sekaligus adalah metode untuk memahami Dia. Dalam kaitan ini, penyataan TUHAN yang kontekstual menyiapkan landasan bagi pelaksanaan misi-Nya dengan menghadirkan dan mengkomunikasikan Injil pada setiap konteks kehidupan masyarakat. Gagasan ini dituangkan melalui diskursus tentang “Pendekatan kontekstual dalam tugas misi dan komunikasi Injil Pasca Pandemi Covid-19” yang mengetengahkan beberapa pokok penting. Pokok-pokok dimaksud antara lain adalah: Pertama, Pendekatan Kontektual dalam Gerakan Misi; Kedua, Pendekatan Kontekstual dalam Komunikasi Injil pada Konteks Pasca Pandemi Covid-19. Diharapkan agar diskursus ini memberikan gambaran mengenai pelaksanaan Amanat Agung Yesus Kristus secara kontekstual dalam kondisi dunia kekinian khususnya pada konteks pasca Pandemi Covid-19.